2020
DOI: 10.3389/fonc.2020.01001
|View full text |Cite
|
Sign up to set email alerts
|

Network-Based Approach to Identify the Antiproliferative Mechanisms of Bruceine D in Breast Cancer From the Cancer Genome Atlas

Abstract: Bruceine D (BD) is a natural compound extracted from a Chinese herb Brucea javanica that has been used for anti-inflammatory and anti-cancer treatment. However, little is reported about BD's effects in breast cancer tumorigenesis. In this paper, we aimed to investigate the effect of BD in breast cancer and elucidate the potential mechanism of BD by integrated multiple databases. Our data suggested BD inhibited MCF-7 and MDA-MB-231 cells proliferation and promoted cells apoptosis. We integrated multiple bioinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Increasing findings support the use of Narciclasine and Bruceine D as antitumor agents [33,46]. Several studies have reported the antitumor mechanisms of the two drugs [47][48][49], but natural products often have multiple molecular targets. Therefore, based on the transcriptome data of 212 breast cell lines treated by different drugs, this study comprehensively explored the underlying antitumor targets for Narciclasine and Bruceine D.…”
Section: Discussionmentioning
confidence: 92%
“…Increasing findings support the use of Narciclasine and Bruceine D as antitumor agents [33,46]. Several studies have reported the antitumor mechanisms of the two drugs [47][48][49], but natural products often have multiple molecular targets. Therefore, based on the transcriptome data of 212 breast cell lines treated by different drugs, this study comprehensively explored the underlying antitumor targets for Narciclasine and Bruceine D.…”
Section: Discussionmentioning
confidence: 92%
“…It is anticipated that there would be 405,680 women in China who are at risk for breast cancer by the year 2025. [8][9][10] Breast cancer is the leading cause of BMS, accounting for about 10% to 30% of metastatic breast cancer cases, second only to lung cancer in BMS rate. [11,12] The molecular mechanism of BMS is still unclear.…”
Section: Declarations All Authors Of This Manuscript Have Confirmed T...mentioning
confidence: 99%
“…It is anticipated that there would be 405,680 women in China who are at risk for breast cancer by the year 2025. [8–10]…”
Section: Introductionmentioning
confidence: 99%